2019
DOI: 10.4103/sni.sni_370_18
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia paucivorans cerebellar abscess: Surgical and pharmacotherapy

Abstract: Background:Nocardia species are ubiquitous in nature and mainly cause pulmonary disease in humans; however, they can also infect the central nervous system and skin. The management of cerebellar nocardiosis is troublesome and requires multiple considerations of the severity of the underlying systemic disease, difficulties in identifying the bacterium, and frequent delay in initiating adequate therapy.Case Description:We report a 52-year-old diabetic female patient with Nocardia paucivorans cerebellar abscesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…N. paucivorans was first isolated in sputum in 2000 [ 58 ]. To our knowledge, 49 cases of N. paucivorans infection have been published [ 2 , 3 , 4 , 56 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], and we summarize these in Table 1 . The majority (33 cases) were reported by Gray et al from Queensland, Australia, and were identified retrospectively via 16S ribosomal DNA sequencing of archived biopsy specimens [ 63 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N. paucivorans was first isolated in sputum in 2000 [ 58 ]. To our knowledge, 49 cases of N. paucivorans infection have been published [ 2 , 3 , 4 , 56 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], and we summarize these in Table 1 . The majority (33 cases) were reported by Gray et al from Queensland, Australia, and were identified retrospectively via 16S ribosomal DNA sequencing of archived biopsy specimens [ 63 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Unfortunately, the paper by Gray et al lacks details regarding therapy and outcome of most patients, limiting the information to be gained from these cases. Additionally, none of the 49 previously reported cases included detailed information on the presumed route of acquisition of N. paucivorans infection [ 2 , 3 , 4 , 56 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…179,181 Antimicrobial therapy may be curative, 181 but mortality rates are high (may exceed 40%). In some cases, surgical debridement, drainage, or resection of brain abscesses may be necessary, [182][183][184][185] particularly in those with impaired immunity. 34,175 In one IC patient with brain abscesses and an intracranial aneurysm due to N. abscessus, a combination of antimicrobials and surgical resection of the aneurysm was curative.…”
Section: Clinical Features Pulmonarymentioning
confidence: 99%
“…38,183,186,187 Nocardia paucivorans, which rarely causes diseases in humans, appears to have a predilection for CNS involvement and dissemination. 38,184,188 Similarly, N. asiatica 33 and N. farcinica have a proclivity for CNS involvement. 34,178,185,189 Bone Bone involvement is rare in nocardiosis, but spine abscesses, 190 epidural abscesses, 191 paravertebral abscesses, 112 mycetomas of the feet, 168 osteomyelitis, 192 and septic arthritis 100,193 have been described.…”
Section: Clinical Features Pulmonarymentioning
confidence: 99%